The governors of Roman Syria in the years of change(AD 324–361): No. XL - Filipczak, Paweł (2020)
This book is devoted to the governors of Syria Coele under Constantine I (after he assumed control of the East in AD 324) and his son Constantine II (AD 337–361), i.e. at a time of major administrative reforms and significant shifts in religious policy. It includes a revision of the list of governors of Syria Coele established by the editors of PLRE I, expanding the current state of knowledge on late Roman prosopography by offering corrections and additions concerning the places of origin, social backgrounds, religious identities, times in office, education and personalities of individual governors. Their actual standing in the local community is also examined, including the influence the provincial elite exercised over the governors’ careers, as is their role in the Christianisation of the province. Among the many sources used in the research, such as rhetorical writings, apologetic and historical works, ecclesiastical histories, chronicles, imperial constitutions, papyri, inscriptions and coins, of special importance are John Malalas’ Chronicle (XIII, 3; the passage is subject to a new interpretation) and the collection of correspondence of the rhetorician Libanius.
Keywords: Syria; Antioch; Constantine the Great; Constantine I; Constantius II; province; governor; administration; Roman Empire